Membrane fluctuations mediate lateral interaction between cadherin bonds - Fenz, Susanne F.; Bihr, Timo; Schmidt, Daniel; Merkel, Rudolf; Seifert, Udo; Sengupta, Kheya; Smith, Ana-Suncana (Nature Physics, 2017)
The integrity of living tissues is maintained by adhesion domains of trans-bonds formed between cadherin proteins residing on opposing membranes of neighbouring cells. These domains are stabilized by lateral cis-interactions between the cadherins on the same cell. However, the origin of cis-interactions remains perplexing since they are detected only in the context of trans-bonds. By combining experimental, analytical and computational approaches, we identify bending fluctuations of membranes as a source of long-range cis-interactions, and a regulator of trans-interactions. Specifically, nanometric membrane bending and fluctuations introduce cooperative effects that modulate the affinity and binding/unbinding rates for trans-dimerization, dramatically affecting the nucleation and growth of adhesion domains. Importantly, this regulation relies on physical principles and not on details of protein-protein interactions. These omnipresent fluctuations can thus act as a generic control mechanism in all types of cell adhesion, suggesting a hitherto unknown physiological role for recently identified active fluctuations of cellular membranes.
Keywords: INTERFERENCE CONTRAST MICROSCOPY; CELL-ADHESION; ADHERENS JUNCTIONS; GIANT VESICLES; I CADHERINS; BINDING; DYNAMICS; DOMAINS; ACTIN; SPECIFICITY